PENGARUH DAYA TARIK DAN WORD-OF-MOUTH TERHADAP KUNJUNGAN ULANG MELALUI KEPUASAN - Fitriandini Dwi Parastiwi; Naili Farida (Universitas Diponegoro, 2017)
Tourism in Indonesia has been growing rapidly. Ketep Pass is one of the natural attractions in Magelang, Regency Central Java in which the number of visits during 2011 to 2015 hasbeen fluctuating. So that the goverment expect to increase visits to attractions Ketep Pass with satisfaction gained from seeing the sights and the positive impact (WOM). The purpose of this study was to identity the effect of attraction and word-of-mouth through satisfaction to re-visit the sights Ketep pass. This type of research is explanatory research, with data collection through questionnaires and interviews. The sampling technique used purposive sampling technique. The Sample was taken from 100 adult visitor respondents who have travelled to Ketep Pass. This study used quantitative analysis techniques. Quantitative analysis using validity, reliability test, the coefficient of correlation, simple and multiple regression analysis, the coefficient of determination, significance test (t test) in one direction, and Sobel test. The results of this research shown that there is a positive effect of natural attractions and word-of-mouth significantly on satisfaction, and satisfaction has a positive effect on return visits. Based on the analysis of Sobel test, known that the variable of natural attractions and word-of-mouth significant effect on satisfaction. Further variables significantly influence the satisfaction of repeat visits. Based on these results it is recommended to increase the repair and maintained the facilities to the tourist attractions as well as add a cultural event which could be an attraction for visitors to visit a tourist attraction Ketep Pass.